2011
DOI: 10.3390/molecules16064828
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids from Praxelis clematidea R.M. King and Robinson Modulate Bacterial Drug Resistance

Abstract: Chemical studies of Praxelis clematidea R.M. King & Robinson resulted in the isolation of six flavones: Apigenine, genkwanine, 7,4’-dimethylapigenin, trimethylapigenin, cirsimaritin and tetramethylscutellarein, which were tested for their toxicity against Staphylococcus aureus SA-1199B, a strain possessing the NorA efflux pump. Efflux pumps are integral proteins of the bacterial membrane and are recognized as one of the main causes of bacterial drug resistance, since they expel antibiotics from the cell. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 32 publications
2
28
0
2
Order By: Relevance
“…These findings indicate that the compounds tested inhibit the activity (or even the expression) of TetK efflux protein, but not of NorA and Msr efflux proteins. This activity may be related to the lipophilicity of the assayed plant compounds, which is a common feature of several putative EPIs, such as methoxylate flavonoids [12], natural amphipathic compounds [13] or even synthetic compounds [14]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings indicate that the compounds tested inhibit the activity (or even the expression) of TetK efflux protein, but not of NorA and Msr efflux proteins. This activity may be related to the lipophilicity of the assayed plant compounds, which is a common feature of several putative EPIs, such as methoxylate flavonoids [12], natural amphipathic compounds [13] or even synthetic compounds [14]. …”
Section: Resultsmentioning
confidence: 99%
“…King and Robinson, Asteraceae family, modulated the NorA efflux protein in S. aureus . In these studies, the antibiotic resistance-modulating effects were also related to the degree of lipophilicity of the tested compounds - particularly the presence of methoxyl groups [17]. …”
Section: Resultsmentioning
confidence: 99%
“…Flavonoids are heterocyclic compouds present in pigment plants in leaves, flowers and fruit. They are divided into 14 classes on the basis of the general structure (Cushnie & Lamb, 2011;Maia et al, 2011;Oh et al, 2011). They have a broad spectrum of biological activity such as antioxidant, anticancer, immunomodulatory, antiviral, antifungal and antimicrobial (Kilani-Jaziri et al, 2011;Fraga et al, 2010;Ozcelik et al, 2011).…”
Section: Plant-derived Compoundsmentioning
confidence: 99%
“…Moreover, those authors proved that due to the lipophilic nature the 3-arylideneflavones influence the cel-membrane integrity causing the bacterial growth inhibition. Another mechanism of antimicrobial activity of flavonoids is modulation of antibiotic resistance (Cushnie & Lamb, 2011;Maia et al, 2011). Maia et al (2011) revealed that six flavones isolated from Praaxelis clematidea.…”
Section: Plant-derived Compoundsmentioning
confidence: 99%
“…[16] Cirsimaritin is flavonoid isolated from Cirsium spp. [17] and exhibits a variety of pharmacological activities including anti-inflammatory, [18] antibacterial, [19,20] antioxidant, [21][22][23][24] anti-anxiety, [25] antispasmodic, [26,27] antiproteinuria, [28] bacterial drug resistance, [29] cyclooxygenase-1 inhibitory, [18] renal protective [30,31] and melanogenic activities. [32] In addition, it has been suggested to have cytotoxic activity against the following human tumour cell lines: gallbladder carcinoma, GBC-SD and GBCSD18H; gastric carcinoma, BGC-823; hepatoma, SMMC-7721.…”
Section: Introductionmentioning
confidence: 99%